Experimental and theoretical biomass char diameter variation during gasification. (15th March 2021) - Wu, Ruochen; Beutler, Jacob; Baxter, Larry L.
Abstract: This investigation explores theoretical and experimental trends in biomass char diameter during gasification by collecting essentially continuous particle size data as a function of time for several fuels under many conditions. A theoretical model describes these variations for an arbitrary char-forming particle over its entire reaction history. The model involves dimensionless exponential parameters that accommodate sintering to swelling. The parameter values do not depend on time or char conversion and provide effective means of describing char diameter. New experimental data from biomass chars illustrate the diameter dependence on burnout under mostly kinetically controlled reaction conditions for a wide variety of initial ash contents, particle sizes, and reaction conditions. The data include continuous measurements of char shape during char conversion from 0 to 99+% compared to a mostly fundamental model describing size change with burnout. The model captures the qualitative and most of the quantitative variation in the data.